Personality-driven kindness content in the context of interpersonal interactions - Ryaguzova, Elena V. (Saratov State University, 2024)
The relevance of the research is due to the fact that in the modern technogenic world, kindness requires special attention because of several reasons: fi rst, kindness is a gift that contributes to the preservation of the humane in a human; second, it resists the devaluation and depersonalization of human individuality; third, it unites people on the basis of deep spiritual values; and fi nally, kindness helps people develop and improve themselves through the expansion of social ties and activation of prosocial behaviors. The objective of the research is to identify how kindness in interpersonal relationships is specifi c to a person depending on its dominant mode. Hypothesis: the subjective experience of receiving and showing kindness in interpersonal interactions determines its content and the specifi cs of verbal referents. Participants: students (N = 75) of Saratov State University (Saratov) aged between 20 and 22 years (M=21.48; SD=1.12), 83% female. Methods (tools): prototypical methodology for describing the structure of the social concept of kindness (P. Verges); semantic diff erential technique to characterize the semantic space of the construct “kind person” (Ch. Osgood); methodology of kindness modes to determine its dominant mode (D. E. Youngs, M. A. Yaneva & D. V. Canter); self-actualization test for the diagnosis of the self-actualization index (E. Shostrom adapted by A. Jones, R. Crandall); behavioral activity questionnaire to determine its type (L. I. Wasserman and N. V. Gumenyuk). Results: the research reveals the structure of the social concept of kindness, constructs the semantic space of the concept “kind person”, identifies the three groups that diff er in relation to themselves and Others, in relation to the modes of kindness, ideas of kindness, behavioral patterns and the specifi cs of verbal referents. Conclusions. The research has worked out the invariant meaning of the concept of good and kindness in diff erent languages; the study has emphasized intersubjective (caring for the Other) and intrasubjective (caring for oneself) psychological orientations of kindness, which are associated with the responsibility of the individual for the present and future of their own and of the Other’s; the research has identifi ed the tendency to understand kindness one-sidedly reducing it to a helping behavior and identifying it with the proper care of the Other; the study has established that the subjective experience of receiving and showing kindness in interpersonal interactions determines the type of the kindness mode and the specifi cs of verbal referents. Practical significance. The results of the study can be used in counseling and psychological training.